2022
DOI: 10.1002/iub.2666
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of endoplasmic reticulum stress and the downstream pathways protects CD4+ T cells against apoptosis and immune dysregulation in sepsis

Abstract: Immunosuppression mediated by CD4 + T cell apoptosis and dysfunction is a key factor in promoting the progression of sepsis. Endoplasmic reticulum (ER) stress participates in the apoptosis and dysfunction of immune cells. We aimed to investigate the role of ER stress inhibition in CD4 + T cells in both in vitro and in vivo models of sepsis. In vitro model of sepsis was established with lipopolysaccharide (LPS) and the rat model of sepsis was established using cecal ligation and puncture (CLP). After the LPS tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Moreover, excessive ER stress induced by LPS-induced inflammation was associated with accelerated apoptosis, characterized by decreased levels of the antiapoptotic protein Bcl-2 and increased levels of the proapoptotic protein caspase-3 . Conversely, inhibition of ER stress had a protective effect, reducing apoptosis . In line with these observations, our study demonstrated that yamogenin significantly inhibited the PERK/eIF2α/ATF4/CHOP signaling pathway in the prefrontal cortex of mice exhibiting depression-like behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, excessive ER stress induced by LPS-induced inflammation was associated with accelerated apoptosis, characterized by decreased levels of the antiapoptotic protein Bcl-2 and increased levels of the proapoptotic protein caspase-3 . Conversely, inhibition of ER stress had a protective effect, reducing apoptosis . In line with these observations, our study demonstrated that yamogenin significantly inhibited the PERK/eIF2α/ATF4/CHOP signaling pathway in the prefrontal cortex of mice exhibiting depression-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…25 Conversely, inhibition of ER stress had a protective effect, reducing apoptosis. 26 In line with these observations, our study demonstrated that yamogenin significantly inhibited the PERK/eIF2α/ATF4/ CHOP signaling pathway in the prefrontal cortex of mice exhibiting depression-like behavior. Furthermore, yamogenin maintained the expression of the antiapoptotic protein Bcl-2 while reducing the levels of the proapoptotic protein caspase-3, providing further evidence of its potential as a neuroprotective agent.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, apoptosis of CD4+ T cells was significantly increased. This phenomenon was improved with the application of ER stress inhibitors ( 83 ). In addition, measuring the expression of IRE1α mRNA and protein in differentiated and reactivated Th2 cells in vitro using qPCR and Western blot showed that the IRE1α/XBP1 pathway is upregulated during helper T cell activation in vitro .…”
Section: Regulation Of Xbp1 In the Immune Microenvironment Of Bone Re...mentioning
confidence: 99%
“…Recognizing the role of ER stress in the pathology of sepsis is important [ 12 ]. Lu et al [ 13 ] found that inhibition of ER stress inhibits apoptosis and immune dysregulation in sepsis. Qian et al [ 14 ] showed that ER-related proteins are significantly expressed in the liver of rats with sepsis, and inhibition of endoplasmic reticulum stress can reduce liver cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%